Prevalence and factors associated with bullying: differences between the roles of bullies and victims of bullying - Georgia Rodrigues Reis e Silva; Maria Luiza Carvalho de Lima; Raquel Moura Lins Acioli; Alice Kelly Barreira (Brazilian Society of Pediatrics, 2020)
Objective: To identify the differences between the prevalence and factors associated with involvement in bullying among schoolchildren from Recife, in the role of victim and perpetrator. Method: This is an epidemiological, cross‐sectional, analytical study, with a probabilistic cluster sample of 1,402 students enrolled in high schools in Recife. Data analysis consisted of a descriptive analysis, followed by the application of Pearson's chi‐squared test with statistical significance of 0.05 and 95% confidence interval. For the association analysis, multilevel modeling was used to control the cluster effect. Results: It was observed that adolescents who feel different from other peers were associated with bullying, regardless of the role played. Being a victim was associated with being female, having low self‐esteem, and using tranquilizers; being a transgressor was a protective factor. As for the role of perpetrator, being male, excessive alcohol consumption, having poor school performance, being a transgressor, and accepting peer violence were the associated variables; in turn, not defending their ideas when among friends showed to be a protective factor for bullying. Conclusion: The differences between the adolescents, whether in the role of victim or perpetrator, indicate that the advocacy and prevention actions should focus on these aspects, mainly in the school environment. Resumo: Objetivo: Identificar as diferenças entre prevalências e os fatores associados ao envolvimento em bullying entre adolescentes escolares do Recife no papel de vítima e agressor. Método: Estudo epidemiológico de corte transversal analítico, com amostra probabilística por conglomerados de 1.402 estudantes matriculados no ensino médio de escolas do Recife. A análise dos dados foi constituída de uma análise descritiva, seguida da aplicação do teste de Qui‐Quadrado de Pearson com significância estatística de 0,05 e Intervalo de Confiança de 95%. Para a análise de associações foi empregada a modelagem multinível para controle do efeito do conglomerado. Resultados: Observou‐se que o adolescente que se sente diferente dos outros colegas apresentou associação com o bullying independente do papel desempenhado. A condição de ser vítima mostrou associação com ser do sexo feminino, ter baixa autoestima e utilizar tranquilizantes, além disso, ser transgressor mostrou ser fator de proteção. No papel de agressor de bullying ser do sexo masculino, fazer uso de álcool em excesso, ter um ruim desempenho escolar, ser transgressor e aceitar violência entre pares foram as variáveis associadas; por sua vez, não defender suas ideias com amigos revelou ser fator de proteção para prática do bullying. Conclusão: As diferenças apresentadas entre os adolescentes, seja no papel de vítima ou de agressor, apontam que condutas de promoção e prevenção tenham enfoque que considerem tais aspectos principalmente no ambiente escolar.